Spontaneous tension pyopneumopericardium–a case with recovery after surgery. Issue 758 (December 1988) - Bilbao-Garay, J.; Carreño, M. C.; Roman, F.; Perez-Maestu, R.; Masa-Vazquez, C.; de Letona, J. M.
Abstract : Tension pyopneumopericardium is a rare condition with a very high mortality. The majority of cases are due to perforation of oesophagus or bronchi into the pericardial cavity. We report a patient with spontaneous pyopneumopericardium who survived with antibiotic treatment and surgical drainage.